Comparison of Microneedling and Glycolic Acid Peels in the Management Acne Scar - Hira Shafquat Memon, Areeba Jabbar, Tooba Malik, Nargis Khan, Maryam Faisal, Asma Javed Kiyani (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the treatment efficacy of microneedling and glycolic acid peels for acne scar treatment. Material and Methods: This randomized controlled trail was carried out at Liaquat University of Medical and Health Sciences, Hyderabad, Sindh during the Period from March, 2022 to August, 2022. We divided 60 patients equally in two groups using blocked randomization. Patients were treat with microneedling in group A while in group B patients were treated with 30% glycolic acid peels. Improvement was assessed by the Goodman and Baron Scale. Chi Square test was used for comparison of effectiveness of treatment in both groups. Results: This study was conducted on 60 patients divided equally in two groups. The mean age in group was 28.57±6.765 years while 30.30±5.932 years in group B. In group A there were 21 (70%) females and 9 (30%) males while in group B there were 20 (66.7%) females and 10 (33.3%) male. In group A 21 (70%) patients were treated effectively while in group B 11 (36.7%) patients were treated effectively (P = 0.01) Conclusion: From our study we conclude that microneedling is an effective treatment for acne scars as compared to glycolic acid peels. Keywords: Acne, Scars, Microneedling, Glycolic acid peels